Synthesis and anti-rheumatoid arthritis activities of 3-(4-aminophenyl)-coumarin derivatives - Yuhang Miao; Jie Yang; Yinling Yun; Jie Sun; Xiaojing Wang (Taylor & Francis Group, 2021)
Rheumatoid arthritis is a chronic systemic disease characterised by an unknown aetiology of inflammatory synovitis. A large number of studies have shown that synoviocytes show tumour-like dysplasia in the pathological process of RA, and the changes in the expression of related cytokines are closely related to the pathogenesis of RA. In this thesis, a series of novel 3-(4-aminophenyl) coumarins containing different substituents were synthesised to find new coumarin anti-inflammatory drugs for the treatment of rheumatoid arthritis. The results of preliminary activity screening showed that compound 5e had the strongest inhibitory activity on the proliferation of fibroid synovial cells, and it also had inhibitory effect on RA-related cytokines IL-1, IL-6, and TNF-α. The preliminary mechanism study showed that compound 5e could inhibit the activation of NF-κB and MAPKs signal pathway. The anti-inflammatory activity of compound 5e in vivo was further determined in the rat joint inflammation model.